Emergence of Carbapenem-Resistant Klebsiella pneumoniae: Progressive Spread and Four-Year Period of Observation in a Cardiac Surgery Division. (4th May 2015) - Lombardi, Fortunata; Gaia, Paola; Valaperta, Rea; Cornetta, Maria; Tejada, Milvana Rosa; Di Girolamo, Luca; Moroni, Alessandra; Ramundo, Federica; Colombo, Alessio; Valisi, Massimiliano; Costa, Elena
Abstract : Frequent use of carbapenems has contributed to the increase to K. pneumoniae strains resistant to this class of antibiotics (CRKP), causing a problem in the clinical treatment of patients. This investigation reports the epidemiology, genetic diversity, and clinical implication of the resistance to drugs mediated by CRKP in our hospital. A total of 280 K. pneumoniae strains were collected; in particular 98/280 (35%) were CRKP. Sequencing analysis of CRKP isolated strains showed that 9/98 of MBL-producing strains carried the b l a VIM- 1 gene and 89/98 of the isolates were positive for b l a KPC- 2 . Antimicrobial susceptibility tests revealed a complete resistance to third-generation cephalosporins and a moderate resistance to tigecycline, gentamicin, and fluoroquinolones with percentages of resistance of 61%, 64%, and 98%, respectively. A resistance of 31% was shown towards trimethoprim-sulfamethoxazole. Colistin was the most active agent against CRKP with 99% of susceptibility. Clonality was evaluated by PFGE and MLST: MLST showed the same clonal type, ST258, while PFGE analysis indicated the presence of a major clone, namely, pulsotype A. This finding indicates that the prevalent resistant isolates were genetically related, suggesting that the spread of these genes could be due to clonal dissemination as well as to genetic exchange between different clones.